The Maqashid Paradox: A Three-Pillar Gap Framework for Understanding Compliance and Social Impact in Indonesian Islamic Banking - Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar; Khaidar Rahmaini Jamila (Yayasan Darussalam Bengkulu, 2026)
Background: The rapid growth of Islamic banking in Indonesia has raised concerns about the gap between formal sharia compliance and the substantive realization of maqashid sharia objectives. Although Islamic banks demonstrate strong compliance performance, evidence indicates that this has not consistently translated into higher maqashid outcomes, raising questions about whether Islamic banking has fulfilled its substantive role in promoting social welfare, justice, and sustainable development. Method: This study employed a qualitative approach using a conceptual-descriptive research design based on a systematic literature review. Relevant studies published between 2017 and 2026 were collected from reputable academic databases including Scopus, Google Scholar, Emerald Insight, and ProQuest. A total of 45 articles were selected and analyzed through thematic synthesis to identify structural factors contributing to the compliance-maqashid gap. Results: The findings reveal three interconnected dimensions underlying the compliance-maqashid gap: regulatory, operational, and human resource factors. Regulatory frameworks remain focused on micro-level contractual compliance rather than substantive maqashid achievement. Operational practices replicate conventional banking models with financing portfolios heavily concentrated in murabahah contracts. Limited maqashid-oriented competencies among banking professionals hinder effective implementation of socio-economic objectives. These conditions collectively reinforce symbolic compliance and sustain a compliance-driven system with limited substantive impact. Conclusion: Achieving maqashid sharia requires a paradigm shift from compliance-oriented governance toward outcome-oriented Islamic banking practices. Strengthening maqashid-based regulations, diversifying financing structures, and enhancing human resource competencies are essential to bridge the gap between formal compliance and substantive maqashid achievement.